Development of pressure-impulse curves for Fiber Reinforced Polymer strengthened reinforced concrete walls - Mutalib, A.; Hao, Hong (2011)
Most research on using Fiber Reinforced Polymer (FRP) to repair and strengthen reinforced concrete structures to resist blast and impact loads are experimentally based. Little quantitative information relating the capacity increament with the FRP strengthening measures is available, and some inconsistent conclusions exist in the literature. It was found that in general FRP strengthening, if it is properly applied onto the RC wall and premature debonding of FRP layers from RC wall is prevented, will increase the wall's capacity in resisting blast loadings. The FRP layer is also a good catchment system to stop concrete debris for personnel protection. In this study, numerical simulations are carried out to construct pressure-impulse (P-I) curves of FRP strengthened RC walls. Damage criteria given in technical manual TM5-1300 based on the support rotation are used. Influences of RC wall and FRP properties on P-I curves are studied. The generated P-I curves can be used in primary assessment of RC wall structural damage to blast loads.